Pendidikan karakter anak usia dini - azzahroh, almas aulia (Maliki Interdisciplinary Journal, 2025)
The purpose of character education in early childhood is to foster commendable behavior that includes elements of worship, social interaction, and values that support life success. This happens in many places, but the family is the child’s first place, where parents are responsible for setting an example. However, schools and communities, through various learning and habituation approaches, are responsible for educating children’s character.In this study, a multidisciplinary approach was used to study the character formation process in TK Aisyiyah Mamajang, Makassar City, which includes philosophical, pedagogical, psychological, and theological elements. The principal, educators, parents, and other early childhood education institutions were the sources of data. The results of the study showed that the character education program in elementary education institutions was successful, which was marked by positive changes in student behavior. It was proven that the BCCT (Beyond Centers and Circle Times) method, together with various habituation and role model activities, helped children become more confident, religious, and independent. This method also helped children become better at communicating. Successful programs showed changes in character, such as changing from spoiled to independent, from shy to more confident, and from undisciplined to more organized.Character education at TK Aisyiyah Mamajang can be an example for other early childhood education institutions in building children’s character from an early age, although there are still some obstacles, such as differences in children’s backgrounds and environmental factors. Character education applied from an early age is expected to form strong people, have noble morals, and are ready to face challenges in the future.